2020
DOI: 10.1101/2020.05.08.083790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbomer-based Nano-Emulsion Adjuvant Enhances Dendritic Cell Cross-presentation via Lipid Body Formation Independent of Glycolysis

Abstract: ADJ induces inflammasome activation in DCs, but deficiency for NLRP3, ASC or caspase 1 did not affect ADJ-mediated cross-presentationNext, we examined the effects of ADJ on the expression profiles of cytokines, chemokines and canonical cell surface markers of DC activation. Compared to untreated DCs, ADJ-treated DCs showed statistically significant, yet modest increases in expression of CD40, CD80, and CD86; no significant differences in expression were observed for MHC-I, MHC-II, or CCR7 (Fig. 1C).ADJ-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
1
1
0
Order By: Relevance
“…Leakage of endosomal antigens into the cytosol is a crucial step in the process of cross-presentation in DCs. Elevated production of reactive oxygen species (ROS) and lipid peroxidation induces the escape of antigens from endosomes to the cytosol, facilitating their degradation and promoting antigen presentation by DCs (93). Consistent with this study, it was observed that increased cellular lipid bodies enhance the antigen crosspresentation of human cDC2s (94), however, whether this process is related to the accumulation of lipid peroxidation remains unclear.…”
Section: Lipid Peroxidation and Dcssupporting
confidence: 68%
“…Leakage of endosomal antigens into the cytosol is a crucial step in the process of cross-presentation in DCs. Elevated production of reactive oxygen species (ROS) and lipid peroxidation induces the escape of antigens from endosomes to the cytosol, facilitating their degradation and promoting antigen presentation by DCs (93). Consistent with this study, it was observed that increased cellular lipid bodies enhance the antigen crosspresentation of human cDC2s (94), however, whether this process is related to the accumulation of lipid peroxidation remains unclear.…”
Section: Lipid Peroxidation and Dcssupporting
confidence: 68%
“…The field of either immunologically silent or immunostimulatory vaccine delivery systems is large and complex (39), and goes far beyond the scope of this article. It includesto name just a few -virosomes (reviewed in (40)) that are among the few adjuvants in a licensed vaccine (41), a wide variety of liposomes, polymers such as carbomer-lecithin adjuvant Adjuplex (42) and PLGA nanoparticles that have been used to deliver various payloads (such as immunostimulatory vaccines for cancer (43) or tolerogenic vaccines for the treatment of autoimmune disease (44), and even immunologically inert materials such as gold particles for the biolistic delivery of DNA vaccines by gene gun (45) (which exert their adjuvant effect through the cellular trauma caused by high-velocity microparticle bombardment of the skin). A delivery system that has recently received unprecedented attention due to the COVID pandemic is lipid nanoparticles (LNPs) that are used in the approved mRNA vaccines BNT162b2/Comirnaty and mRNA-1273/Spikevax.…”
Section: (Re)-defining What Is An Adjuvant: the Role Of "Carriers" Su...mentioning
confidence: 99%